Aging Evaluation Programs for Jet Transport Aircraft Structural Integrity - Galović, Borivoj; Steiner, Sanja; Bazijanac, Ernest (Promet - Traffic&Transportation, 2012)
The paper deals with criteria and procedures in evaluationof timely preventive maintenance recommendations that willsupport continued safe operation of aging jet transports untiltheir retirement from service. The active service life of commercialaircraft has increased in recent years as a result of low fuelcost, and increasing costs and delivery times for fleet replacements.Air transport industry consensus is that older jet transportswill continue in service despite anticipated substantial increasesin required maintenance. Design concepts, supportedby testing, have worked well due to the system that is used to ensureflying safety. Continuing structural integrity by inspectionand overhaul recommendation above the level contained inmaintenance and service bulletins is additional requirement, insuch cases. Airplane structural safety depends on the performanceof all participants in the system and the responsibility forsafety cannot be delegated to a single participant. This systemhas three major participants: the manufacturers who design,build and support airplanes in service, the airlines who operate,inspect and mantain airplanes and the airworthiness authoritieswho establish rules and regulations, approve the design andpromote airline maintenance performance.